Griewe in Suid-Afrikaanse hospitale: 'n Geskiedkundig-verpleegkundige perspektief - S. Potgieter; M. Muller (AOSIS, 1998)
The nursing service manager is accountable for adequate and efficient personnel management in the nursing service and the management of grievances is an important aspect of the personnel management function. The question arises, however, how and when grievances in nursing services arose and developed? The purpose of this article is to give a historical description of the development and management of grievances in nursing services for the time frame 1652-1990. An historical analysis was undertaken by means of news paper analysis, as well as other written resources. The results show that the development of grievances are related to the development of hospitals in South Africa and that grievances were poorly managed. The following conclusions are made: * grievances in nursing are related to the establishment of hospitals; * the first official grievance was lodged in 1824 by a surgeon; * grievance are mainly related to the working conditions, remuneration and management; * complaints with salaries and food were lodged by nurses as early as 1869; * it appears as if nursing service managers are not adequately skilled in the management of grievances experienced by nursing staff - the same mistakes are made leading to strike action by nurses/midwives; * unhappiness with the inappropriate manner in which grievances are managed lead to industrial action by nursing staff since 1889. Continuous empowerment of nursing services managers in the management of grievances is important and therefore the development of a model for grievance management in nursing services is also recommended.